Identification of the FRAXE fragile site in two families ascertained for X linked mental retardation. Issue 2 (February 1993) - Flynn, G A; Hirst, M C; Knight, S J; Macpherson, J N; Barber, J C; Flannery, A V; Davies, K E; Buckle, V J
Abstract : Chromosome fragility in two families not exhibiting amplification of the CGG trinucleotide associated with the fragile X site has been examined. Fluorescence in situ hybridisation with cosmid DNA from loci immediately flanking FRAXA and other distal loci have confirmed that cytogenetic fragility in these subjects is the result of expression of a new folate sensitive fragile X site, FRAXE.